Wits, fittes and fancies: Spanish ingenio in Renaissance England = Wits, fittes and fancies: “ingenio” español en la Inglaterra renacentista - Shaw, Patricia (Estudios Ingleses de la Universidad Complutense, 2004)
This paper will be introduced by a brief a comparative analysis of the terms wit and ingenio, to be followed by an equally brief reference to those “witty” Spanish works which aroused most interest in Renaissance England thanks to the English translations and adaptations thereof. A more detailed analysis will then be offered of the English version of a particularly interesting Spanish work devoted to “diversas e ingeniosas invenciones… de nuestra nación”, i.e. Anthony Copley’s Wits, fittes and fancies… (1595) based on Melchor de Santa Cruz de Dueñas’ Floresta española de apotegmas y sentencias… (1574), a little time if possible, being set aside for a discussion of the life and adventures of A. Copley, a picaresque character himself, in all conscience! Finally, some attention will be paid to examples of verbal wit on the part of real-life Spaniards as reported by seventeenth-century English letter-writers, historians, biographers and travellers.